Peran UMKM Bakso dalam Meningkatkan Perekonomian Masyarakat di Desa Singa - Ripa Sabila Usni Sitompul; Adeliya Saragih; Juliana Nasution (Jurnal Pengabdian Masyarakat Waradin, 2026)
This study aims to examine in depth the contribution of meatball micro, small, and medium enterprises (MSMEs) to local economic development in Singa Village. As a business sector closely aligned with community needs, meatball MSMEs have significant potential to create job opportunities, increase community income, and stimulate local economic activity. This study employed a qualitative approach with a literature review method, focused on collecting and analyzing information from various relevant sources, such as journals, research reports, and policy documents related to MSME empowerment. The study results indicate that the existence of meatball MSMEs not only serves as a source of income for entrepreneurs but also creates a ripple effect on the economy, such as increased demand for local raw materials and the opening of other supporting business opportunities. These findings are expected to serve as a reference for the village government, related organizations, and stakeholders in formulating strategies for empowering meatball MSMEs as a key sector for sustainable economic development in Singa Village. Therefore, it can be concluded that meatball MSMEs contribute significantly to village economic growth.